2022
DOI: 10.1002/brb3.2790
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in behavioral variant frontotemporal dementia

Abstract: Introduction: Functional connectivity (FC)-which reflects relationships between neural activity in different brain regions-has been used to explore the functional architecture of the brain in neurodegenerative disorders. Although an increasing number of studies have explored FC changes in behavioral variant frontotemporal dementia (bvFTD), there is no focused, in-depth review about FC in bvFTD. Methods: Comprehensive literature search and narrative review to summarize the current field of FC in bvFTD. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…On the one hand, indirect evidence suggests that the proposed preference for less abstract concepts in PD may not be mirrored in this disease 4 , 44 . On the other, semantic variability may be similarly altered in bvFTD, which also involves marked inhibitory deficits 45 and disruptions of key correlates, such as the salience network 46 . More generally, while lexico-semantic deficits are pervasive in PD 2 , 47 , they emerge less consistently in bvFTD 43 , 48 , likely supporting individual patient identification in the former but not in the latter population.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, indirect evidence suggests that the proposed preference for less abstract concepts in PD may not be mirrored in this disease 4 , 44 . On the other, semantic variability may be similarly altered in bvFTD, which also involves marked inhibitory deficits 45 and disruptions of key correlates, such as the salience network 46 . More generally, while lexico-semantic deficits are pervasive in PD 2 , 47 , they emerge less consistently in bvFTD 43 , 48 , likely supporting individual patient identification in the former but not in the latter population.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, we did not observe a stronger correlation between the seed in the posterior cingulate cortex and other parts of the DMN in patients than in controls, which is in line with a recent review that found inconsistent evidence for this hypothesise. 18…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Whilst there is heterogeneity in the pattern of atrophy and heterogeneity in respect to underlying neuropathology of bvFTD, studies have demonstrated a consistent core of neurodegeneration involving the AI and ACC across all cases of bvFTD. 15,16 This characteristic pattern of neurodegeneration is further reflected in reduced functional connectivity of the AI and ACC, which may be identified using resting state functional MRI 17,18 . The AI and the ACC (its posterior part, sometimes referred to as midcingulate cortex, MCC) have been shown to be central nodes in the ventral attention network (VAN), 19 also referred to as the “salience network”.…”
Section: Introductionmentioning
confidence: 99%
“…Functional changes were studied using resting-state functional magnetic resonance imaging (rsfMRI), providing measures of spontaneous brain activity and functional connectivity (FC) (Azeez & Biswal, 2017 ). Decreased FC in bvFTD was reported within/between lateral prefrontal, basal ganglia, insular, hippocampal and amygdalar regions as well as salience and default mode networks (Ferreira et al, 2022 ; Kamalian et al, 2022 ). Conversely, increased FC was reported within the default mode network (Filippi et al, 2013 ; Whitwell et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%